THE URGENCY OF THE STATE SECRETS BILL FROM A HUMAN RIGHTS PERSPECTIVE - Dwi Kurniawan, Itok; Utomo , Agata Ferisa (EVOKASI: Jurnal Kajian Administrasi dan Sosial Terapan, 2024)
The Draft State Bill Law has been a topic of discussion since the early reform era. However, this draft law often generates polemics among the press and democracy activists because it is considered to reverse the pace of reform that has been fought for. In the end, the House of Representatives decided to include this State Secrets Bill in the National Legislation Program (Prolegnas). This bill will be a legal regime for state secrets which will be a guideline for all State Institutions in matters of state secrecy which includes documents, objects, property and so on. This bill is also being pushed on the grounds that currently Indonesia does not have definite regulations regarding the protection and safeguarding of state secrets. Thus, it is hoped that this bill will be a breath of fresh air for the protection of state secrets in order to ward off threats to state defense and security. However, this bill faces challenges in being able to balance the public's right to access information and openness as stipulated in Article 28F of the 1945 Constitution of the Republic of Indonesia.